A Analisis Fosil Foraminifera Formasi Wonosari dan Formasi Oyo Pembentuk Morfologi Karst Gunung Sewu Bagian Timur - Aliyan, Silmi Afina; Christanti Agusta, Vera; Syaeful Bahri, Ayi (CV. Multi Kreasi Media, 2023)
Gunungsewu is one of the areas that has the second largest karst landscape in Indonesia. The diversity of morphology in the karst hill area makes this area interesting for research, especially by researchers in the field of geology. In the western region towards Gunung Kidul the formation of karst produces a morphology in the form of conical hills and in the eastern region towards Pacitan produces a morphology dominated by the formation of vertical caves. The Pacitan area is still limited in terms of information on the characteristics of the limestones that make it up, including the fossils that make up the limestones in this area. This paper describes the diversity of foraminifera fossils that make up the Wonosari and Oyo formations. Comparison of samples from the two formations, both planktonic and benthic fossils, shows the age and depositional environment of these two formations. The diversity of foraminifera fossils found in these two formations provides a new perspective on the age order in the Gunungsewu karst area. The presence of abundant Groborotalia mayeri fossils in both formations, which are well preserved, indicates that the Pacitan karst area was formed in the Middle Miocene. Meanwhile, the presence of benthic fossils indicates a deep littoral to neritic depositional environment from the Wonosari Formation and the Oyo Formation